2016
DOI: 10.1016/j.theriogenology.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Implications of glycolytic and pentose phosphate pathways on the oxidative status and active mitochondria of the porcine oocyte during IVM

Abstract: Glycolysis and the pentose phosphate pathway (PPP) were modulated in porcine cumulus-oocyte complexes during IVM by the addition of inhibitors and stimulators of key enzymes of the pathways to analyze their influence on the oxidative status, active mitochondria, and maturation of the oocyte. The influence of pharmacologic and physiological inhibitors of glycolysis (Sodium fluoride and ATP) and PPP (6-Aminonicotinamide and nicotinamide adenine dinucleotide phosphate) was validated by assessing glucose and lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…In an in vitro oocyte culture system, a decrease in glucose concentration was shown to significantly inhibit meiotic divisions, subcapsular maturation, and subsequent embryonic development in bubaline and bovine oocytes[4, 5]. Moreover, the addition of a sufficient amount of glucose to the IVM medium significantly enhances IVM and subsequent developmental capacity of bovine and porcine oocytes [68]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro oocyte culture system, a decrease in glucose concentration was shown to significantly inhibit meiotic divisions, subcapsular maturation, and subsequent embryonic development in bubaline and bovine oocytes[4, 5]. Moreover, the addition of a sufficient amount of glucose to the IVM medium significantly enhances IVM and subsequent developmental capacity of bovine and porcine oocytes [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have reported effects of glucose metabolism on oocyte maturation, knowledge of the underlying mechanism(s) is still limited [8, 13]. Moreover, even though other studies have observed that glucose metabolism during oocyte maturation can significantly affect in vitro fertilization and subsequent post-embryonic development [11, 1417], the effect of glucose metabolism on oocyte cytoplasm maturation has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…During the progression of meiosis to the MII stage, mammalian oocytes consume glucose simultaneously through more than one metabolic pathway (33). Glycolysis and the PPP seem to play key roles in this process, as inhibition of these metabolic pathways perturbs nuclear maturation, oxidative metabolism, and active mitochondria within oocytes, resulting in impaired developmental capacity (2,38,40). The glycolytic pathway accounts for a considerable amount of glucose consumption by COCs and allows for energy generation in the form of ATP and metabolites that can be readily utilized by the oocytes, such as pyruvate and lactate (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in mouse and porcine species, increased glucose metabolism through glycolysis and PPP facilitates oocyte cytoplasmic maturation by supplying energy (38,40). However, the inhibition of glycolysis and PPP results in the delayed progression of nuclear maturation (2). Several studies have demonstrated that glucose is able to influence oocyte maturation in the absence of cumulus cells and that carrier-mediated uptake of pyruvate and glucose is essential for oocyte function (24,36).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that glycolysis is high in cumulus cells [27,28]. However, oocytes use mainly aerobic metabolic pathways, and glycolysis is almost undetectable in this cell [29]. Cumulus cells metabolize glucose, producing glycolytic metabolites such as pyruvate and/or lactate, which can be further metabolized by the oocyte [30,31].…”
Section: Discussionmentioning
confidence: 99%